Hetero-polycyclic aromatic systems: A data-driven investigation of structure–property relationships - Chakraborty, Sabyasachi; Mayo Yanes, Eduardo; Gershoni-Poranne, Renana (Beilstein Journal of Organic Chemistry, 2024)
Polycyclic aromatic systems (PASs) are pervasive compounds that have a substantial impact in chemistry and materials science. Although their specific structure–property relationships hold the key to the design of new functional molecules, a detailed understanding of these relationships remains elusive. To elucidate these relationships, we performed a data-driven investigation of the newly generated COMPAS-2 dataset, which contains ~500k molecules consisting of 11 types of aromatic and antiaromatic rings and ranging in size from one to ten rings. Our analysis explores the effects of electron count, geometry, atomic composition, and heterocyclic composition on a range of electronic molecular properties of PASs.
Keywords: computational chemistry; database; dataset; π-conjugated; polycyclic aromatic hydrocarbons; polycyclic aromatic systems